Existence of complex structures on decomposable Lie algebras - Sroka, Marcin (Universitatis Iagellonicae acta mathematica, 2020)
We provide the classification of the six-dimensional decomposable Lie algebras, with the dimension of the biggest indecomposable summand less than five, admitting complex structures. 2010 Mathematics Subject Classification. 17B40, 53C15, 53C30.